Pengaruh Strategi Pembelajaran Kooperatif Tipe STAD Versus Ekspositori dan Gaya Kognitif terhadap Hasil Belajar Konsep Fisika Siswa Kelas X SMA - Prayekti -- (Jurnal Pendidikan dan Kebudayaan, 2014)
This research aims to examining: 1) The learning outcomes differences on the understanding and application of physics concept between groups of students who learned through STAD cooperative learning and expository learning; 2) The learning outcome differences on physics concept understanding and application among students with different cognitive styles; 3) The learning outcome influences of physics comprehension; 4) The interaction effect between learning and cognitive style on learning outcomes of physics. This research used a quasiexperimental research with factorial of non-equivalent control group design, which is implemented in four classes, determined by lottery, such as XMIA A class, XMIA B class, XMIA C class, XMIA D class at SMAN 58 Jakarta Timur with 144 students altogether. Two classes were as the experimental classes and two other class were as the control classes. Learning outcomes data were collected through pretes and pos tes and analyzed by using statistical MANCOVA test helped by SPSS 15. The result showed that: 1) STAD learning strategy demonstrate learning outcomes of comprehension and application of physics concept is better than expository learning strategies; 2) students who have field independent cognitive styles demonstrate learning outcomes of comprehension physics concepts is better than students who have a field dependent cognitive style; 3) there is an interaction between learning strategies and cognitive style on learning outcomes of comprehension physics concepts; and 4) there is no interaction between learning strategies and cognitive style on learning outcomes of physics concepts application. STAD learning strategy demonstrate learning outcomes of comprehension and application of physics concept is better than expository learning strategies.